Clinical relevance of bcl-2(MBR)/J(H) rearrangement detected by polymerase chain reaction in the peripheral blood of patients with follicular lymphoma. - Bertoni, F. (Nature Publishing Group, 1997)
We evaluated the prognostic role of peripheral blood polymerase chain reaction (PCR) assay for detection of the bcl-2(MBR)/J(H) rearrangement in 59 patients with follicular lymphoma (FL) treated at our centre since 1989. Thirty-five (59%) patients were bcl-2/J(H) positive and 24 (41%) were negative in the peripheral blood at diagnosis. Peripheral blood bcl-2/J(H) rearrangement detection at diagnosis had no relation to overall survival (OS) and time to progression (TTP). Peripheral blood PCR assay was performed post treatment in 17 patients who were bcl-2/J(H) positive at diagnosis. Fourteen of the patients (82%, 95% CI 56-96%) became bcl-2/J(H) negative. Nine of these patients were further analysed during follow-up and, after several months, circulating cells carrying the bcl-2/J(H) rearrangement reappeared in five of the nine patients. Peripheral blood clearance of bcl-2/J(H)-positive cells was correlated with better overall survival (log-rank P < 0.05) but not with TTP. Our data confirmed that bcl-2(MBR)/J(H) rearrangement detection by PCR at diagnosis is not a prognostic factor in follicular lymphoma. In our series, clearance of circulating bcl-2/J(H)-positive cells appeared to correlate with better overall survival. Post-treatment examination of the peripheral blood by PCR may have clinical relevance for prediction of the survival pattern of the patients.